2022
DOI: 10.32832/jm-uika.v13i1.5123
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Peluang Usaha Urban Farming: Pengembangan Hidroponik di Desa Karangwidoro Kab. Malang

Abstract: <p><em>The growth of population in the world-wide is inline with the demand of food and land-use. However, the availability of land to produce food is tragically scarce. One of the solution which popular among society is by doing urban farming. Urban farming is a farming concept that is used as a solution in the midst of dense urban buildings and the lack of land for farming. There are various types of urban farming which one of the most popular is hydroponics. Hydroponics is considered as agricult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…Elements in vertical farming, such as viticulture or polybags, can utilize land that is not too large of urban agriculture (Septya et al, 2022). Vertical farming technology can maintain urban food production for the next few years (Okuputra et al, 2022). If implemented correctly, Viticulture urban farming can overcome problems such as food self-sufficiency, air pollution, and green open spaces (Luthan et al, 2019).…”
Section: Vertical Farmingmentioning
confidence: 99%
See 1 more Smart Citation
“…Elements in vertical farming, such as viticulture or polybags, can utilize land that is not too large of urban agriculture (Septya et al, 2022). Vertical farming technology can maintain urban food production for the next few years (Okuputra et al, 2022). If implemented correctly, Viticulture urban farming can overcome problems such as food self-sufficiency, air pollution, and green open spaces (Luthan et al, 2019).…”
Section: Vertical Farmingmentioning
confidence: 99%
“…The case study tries to identify the available areas for implementing urban agriculture in Malang City. For example, a preliminary study found that urban agriculture can improve food access and distribution in low-income communities (Atasa & Nugroho, 2021;Giriwati et al, 2018;Kamil & Romadhan, 2020;Nasuiton, 2020;Okuputra et al, 2022). Additional studies have investigated the role of urban agriculture in increasing equity of access to healthy food, examined the economic life of smallholder farmers, and addressed challenges in sustainable agriculture (Arifah & Poerbaningtyas, 2023.;Artandio et al, 2019;Ilham Pradana;& Wandari, 2023;Murwani et al, 2022;Setiyo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Budidaya hidroponik merupakan hal baru bagi Kampung Songo. Berdasarkan wawancara dengan pengurus Kampung Songo adalah pengelolaan hidroponik mempunyai beberapa kendala yang harus dihadapi(Adryan Okuputra et al, 2022). Masalah pertama pada suhu air yang dialirkan tetap terjaga dengan baik dan tidak terlalu panas.…”
Section: Gambar 2 Lahan Kosong Green Houseunclassified
“…Hal inilah yang semakin memikat para konsumen serta pembuka peluang usaha untuk tetap fokus dalam berkarya. Selain peluang usaha di bidang hidroponik dapat menjajikan untuk meningkatkan kesejahteraan masyarakat, hidroponik juga dapat meningkatkan kualitas udara menjadi lebih baik karena hidroponik merupakan sistem budidaya tanaman yang mampu membuat udara lingkungan sekitar jadi lebih segar dan sejuk (Alma & Buchari, 2007;Okuputra et al, 2022;Susilaningsih & Hidayat, 2018). Penyebab utamanya adalah sistem ini tidak memakai bahan kimia untuk pemupukan dan penanggulangan hama dan serangan penyakit.…”
Section: Pembahasanunclassified